Five weeks cross-training effects on the physical performance of elite football referees in Benin - Tiama, Adama; TONON, Brigitte Affidéhomé; NOUATIN, BASILE; Quenum, Coffi Alphonse; KABORÉ, André (My University, 2023)
Introduction: Cross-training is effective in developing the physical abilities of athletes, but its short-term effects are little known among referees. The purpose of this study was to determine the effects of a five-week cross-training block on the physical performance of soccer referees. Methods: It was carried out with 18 elite referees in Benin, divided into two equal groups: one experimental group (EG) and the other control group (CG), respectively subject to cross-training and ordinary training. The tests of squat jumps, counter movement, isolated sprints over 10 m, over 40 m, Illinois agility, capacity for repeated sprints and the Yo-Yo IRT2 were carried out before (M1) and after (M2) training. The Wilcoxon and Mann Whitney U rank tests were used for comparisons between M1 and M2, then between EG and CG. Results: At the end of training, 2 x VO ma (+2.8% versus +0.2%; p = 0.0004), squat jump height (+8.1% versus +0.7%; p = 0.002), counter movement (+6.0% vs +1.0%; p = 0.04), performance in isolated sprint tests over 10 m (−3.7% vs −0.0%; p = 0.02), 40 m (−16.4% vs −0.04%; p = 0.0003), Illinois Agility (−1.3% vs −0.5%; p = 0.03), repeated sprints (−2.1% vs −0.1%; p = 0.001) were more improved in GE than in GC. Conclusion: In five weeks, cross-training improved the physical abilities that determine the performance of the football referee. Its long-term effects will need to be assessed to complete these results.
Keywords: Football referees; Cross-training; Physical tests; Benin Republic